Larval Biometry of Simulium rubrithorax (Diptera: Simuliidae) and Size Comparison between Populations in the States of Minas Gerais and Roraima, Brazil - Alvan-Aguilar, Miriam Adriana (Memórias do Instituto Oswaldo Cruz, 2020)
The number of larval instars of Simulium (Hemicnetha) rubrithorax Lutz (Diptera: Nematocera) was determined using the lateral length of the head capsule. In this study 1,035 larvae, of different sizes, were measured (639 from the state of Roraima and 396 from the state of Minas Gerais). A frequency distribution analysis was carried out on the measurements of the lateral length of the head capsule to determine the number of larval instars. The limits of each instar were defined by the lower frequency of the measurements falling in a range of values, by the presence of the "egg burster" that characterizes the first larval instar, and by the developmental stage of the gill histoblast. The determination of the instar number was tested using a Student's t-test (p < 0.05), the Dyar rule and the Crosby growth rule. The results indicate the existence of 7 larval instars for this species, although this result was not in accordance to the Crosby rule. Last-instar larvae from two widely separated geographical populations (Roraima and Minas Gerais), collected in habitats with different water temperature were compared and no differences (p > 0.05) were observed between them.